Performance simulation of a parallel dual-pressure once-through steam generator - Chen, Yu-Zhi; Li, Yiguang; Newby, Michael A. (Elsevier, 2019)
The increasing demand for electricity and concern about global warming mean that electric power generation is required to be more efficient, cleaner, and more cost-effective. Combined-cycle power plants have gradually replaced their simple-cycle counterparts to generate more useful power by adding a bottom cycle to recover more energy from prime mover exhaust gas. There are two types of devices used to produce steam—one is the conventional drum-type heat recovery steam generator, and the other is the once-through steam generator (OTSG). The performance simulation of the former is relatively mature but is more difficult for the later. In this research, a novel simulation method for the thermodynamic performance of a parallel dual-pressure OTSG under both design and off-design operating conditions has been developed. The method has been applied to an OTSG operating in a combined-cycle gas turbine power plant at Manx Utilities, Isle of Man in the UK to demonstrate the effectiveness of the method. Meanwhile, the OTSG performance variation caused by inlet gas energy variation and downstream steam turbine erosion are demonstrated. The simulation results of the OTSG show good agreement with field data. The proposed method may be useful for both researchers and engineers in relevant area.
Keywords: Once-through steam generator; Performance; Simulation